Digital differential protection technique of transmission line using instantaneous active current: theory, simulation and experiment. Issue 11 (1st August 2015) - Deng, Xiangtian; Yuan, Rongxiang; Li, Timing; Liu, Wang; Shen, Yangwu; Xiao, Zhenfeng
Abstract : Current differential protection is widely used as the main protection in UHV/EHV (Ultra/Extra High Voltage) transmission lines with advantages of simple principle, high reliability and inherent phase‐selection capacity. However, as the voltage level and line length increase, the performance of the current differential protection is severely restricted by distributed capacity current. Aimed at this problem, a rapid extraction method of single‐phase active current is proposed in this paper. The method first uses single PLL (phase‐locked loop) to track the phase of the corresponding fundamental voltage. Then the current signal is transformed from the abc static coordinate system to the pq rotating coordinate through transformation matrix. By filtering out the high‐frequency AC signal on p axis with low‐pass filter, the active current component remaining being in the same direction with voltage phase can be obtained. On this basis, a novel active current differential protection method is proposed, with the advantages of high sensitivity and strong capacity of enduring transition resistance without requirement for the acquisition of line impedance parameters. Finally, the proposed method is tested by a series of dynamic simulations through PSCAD and experiment. The simulation results show that the method has merits of effectiveness, robustness and rapidity.